MOLECULAR CHARACTERIZATION AND PHYLOGENETIC RELATIONSHIP OF DIFFERENT CITRUS VARIETIES OF PAKISTAN - S. Naz; K. Shahzadi; S. Rashid; F. Saleem; A. Zafarullah; Shabbir Ahmad (Journal of Animal and Plant Sciences, 2014)
Genetic relationship among 17 citrus commercially important cultivars, including local and some hybrid varieties of Pakistan was evaluated by RAPD (Random Amplified Polymorphic DNA) markers. Fifteen decamer primers were selected out of 25 primers that produced 153 polymorphic bands with 13bands per primer on an average with a total of 188 bands. To analyze the genetic similarity or dissimilarity Jaccard Coefficients was used. The dendrogram that separated 17 citrus genotypes into 4 main clusters was generated by using UPGMA. Across all the genotypes the genetic similarity value observed were 0.66 with the two cultivars of Kinnow and Seedless kinnow (Mandarin) and two cultivars of Meiwa and Marumi (Kumquat) showing maximum similarity value (0.85).Genetic difference among the citrus varieties was high that depicted that they do not belong to similar origin.
Keywords: Genetic diversity; Citrus varieties; RAPD; Polymerase chain reaction; phylogenetic relationship